2012
DOI: 10.1163/157075611x617094
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use, but not dispersal limitation, as the mechanism behind the aggregated population structure of the mygalomorph species Atypus affinis

Abstract: International audienceDispersal and habitat selection are the main factors that affect the distribution of species in spatially structured habitat. Species typically occurring in an aggregated way are supposed to experience dispersal limitation or to be highly selective for specific habitat attributes in their environment. In order to understand the distribution pattern of a mygalomorph spider species, Atypus affinis, we conducted an intensive survey to detect correlations of spider densities with specific hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The deep population structure recovered in active ground dwelling hunters could be explained by the high habitat fidelity of ground species. Such habitat fidelity would result in more fragmented suitable habitat patches, and consequently less connected populations, as has been observed in the purse-web spider Atypus affinis Eichwald, 1830 (Pétillon et al, 2012). In fact, Malumbres-Olarte et al (2020) found ground-dwelling species to have higher levels of endemicity than species living higher in the vegetation.…”
Section: Uncovering Geographic Patterns Of Intraspecific Genetic Vari...mentioning
confidence: 94%
“…The deep population structure recovered in active ground dwelling hunters could be explained by the high habitat fidelity of ground species. Such habitat fidelity would result in more fragmented suitable habitat patches, and consequently less connected populations, as has been observed in the purse-web spider Atypus affinis Eichwald, 1830 (Pétillon et al, 2012). In fact, Malumbres-Olarte et al (2020) found ground-dwelling species to have higher levels of endemicity than species living higher in the vegetation.…”
Section: Uncovering Geographic Patterns Of Intraspecific Genetic Vari...mentioning
confidence: 94%
“…We measured ballooning as a binary variable, i.e., as the presence/absence of this behavior at the end of the 26-day study period. Two hours after acclimation and treatment with neonicotinoids, we stimulated ballooning by simulating a slight breeze at 2 m s −1 with a ventilator and by placing the tested spiders in dishes with vertical wooden sticks as described by Pétillon et al 60 . This environment stimulated the control spiders to climb to the very tops of the sticks, where they adopted a tiptoe position and produced gossamer silk from their abdomens.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of mygalomorph species exhibit the SRE traits of low mobility, low dispersal, low fecundity, slow growth, restriction to particular habitats, and entire distribution being less than 10,000 km 2 ( Harvey, 2002 ). Some mygalomorph species have capacity to balloon ( Pétillon et al, 2012 ), but this may have evolved to mitigate territorial behaviour (L. D. Mason, 2017, unpublished data) rather than to increase dispersal capability. As such, the biology of particular SRE groups will still need to be considered in management for conservation.…”
Section: Discussionmentioning
confidence: 99%